2017
DOI: 10.21149/9149
|View full text |Cite
|
Sign up to set email alerts
|

The hidden burden of Chikungunya in central Mexico: results of a small-scale serosurvey

Abstract: Objective. To estimate the seroprevalence of CHKV antibodies and assess correlates of seropositivity at a small geographical scale. Materials and methods. A community-based serosurvey of 387 households in Puente de Ixtla, Morelos (central Mexico). Serum IgG antibodies to CHKV were detected by immunoassay. Results. From 27 April to 29 May 2016, we interviewed and collected blood samples from 387 individuals at the same number of households. A total of 114 (29.5%) participants were seropositive to CHK, 36 (31.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Most knowledge on the early dynamics of CHIKV transmission in the Americas has been derived from passive case-patient reporting [3,[25][26][27][28][29] or cross-sectional serological surveys [6][7][8][9][11][12][13]26,[30][31][32]. Passive national surveillance systems based on mandatory case reporting have low sensitivity because patients misdiagnosed as having another disease are not reported, and those less symptomatic may not seek health care [33][34][35]; the former is especially important for CHIKV infection, which is easily confused with dengue or even Zika [36].…”
Section: Discussionmentioning
confidence: 99%
“…Most knowledge on the early dynamics of CHIKV transmission in the Americas has been derived from passive case-patient reporting [3,[25][26][27][28][29] or cross-sectional serological surveys [6][7][8][9][11][12][13]26,[30][31][32]. Passive national surveillance systems based on mandatory case reporting have low sensitivity because patients misdiagnosed as having another disease are not reported, and those less symptomatic may not seek health care [33][34][35]; the former is especially important for CHIKV infection, which is easily confused with dengue or even Zika [36].…”
Section: Discussionmentioning
confidence: 99%
“…While certain studies conducted in Mexico revealed that specific climate factors are strong drivers for these ABDs 25 27 , other studies suggested socioeconomic factors were the strongest predictors in the spread of arthropod-borne (or arbovirus) transmission in some parts of Mexico 28 30 . Despite Mexico being a country highly endemic to CHIKV, DENV, and ZIKV 4 , 5 , 31 , 32 , there is no national study to date in which long-time series data have been combined with spatiotemporal socio-demographic risk factors and climatic parameters. Understanding the spatiotemporal and socio-demographic risk factors (e.g.…”
Section: Introductionmentioning
confidence: 99%